Brain iron deposition in essential tremor: A quantitative 3‐tesla magnetic resonance imaging study. Issue 2 (12th December 2012) - Novellino, Fabiana; Cherubini, Andrea; Chiriaco, Carmelina; Morelli, Maurizio; Salsone, Maria; Arabia, Gennarina; Quattrone, Aldo
<x xml:space="preserve">Abstract</x> Studies have demonstrated brain iron deposition in neurodegenerative disease and in normal aging. Data on this topic are lacking in essential tremor (ET). The aim of our study was to investigate brain iron content in patients with ET, using quantitative magnetic resonance imaging (MRI) T2*‐relaxometry. We enrolled 24 patients with ET and 25 age‐matched healthy controls. Subjects were examined using a 3T MRI scanner. The protocol included conventional MRI sequences and quantitative T2*‐relaxometry. Whole‐brain voxel‐based analyses showed significant differences in T2* values in bilateral globus pallidus, substantia nigra, and in right dentate nucleus (P < .001 uncorrected). In the bilateral pallidum, differences survived family‐wise‐error (FWE) correction for multiple comparisons (P < .05). The present study provides the first evidence of increased brain iron accumulation in ET patients. Our results are suggestive of a possible involvement of motor systems outside of the cerebellum/cerebellar pathway and, more specifically, of the globus pallidus. © 2012 Movement Disorder Society